Parenting Narratives Among Methamphetamine Using Mothers and Fathers - Beaton, Blake (Crime & delinquency, 2023)
We examine the narratives of parents and stepparents who used methamphetamine to uncover how they talk about parenting decisions relating to their children using drugs. We find that parents draw on themes of protecting children from harm to justify their decisions and to frame themselves as responsible parents. Whereas most said that they would not use with their children, those who did justified their choices by saying they were protecting their children. Regardless of whether they used with their children or not, parents narratively framed their decisions in ways that they believed reflected parenting beliefs common in their social setting. Our findings suggest that one?s ability to frame parenting decisions in culturally accepted practices can facilitate intergenerational drug use.